USING DRAW LABEL CAPTION (DLC) STRATEGY TO IMPROVE NARRATIVE WRITING ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF MAN SAKATIGA INDRALAYA - INTIFADHAH INTIFADHAH; RITA INDERAWATI; HARISWAN PUTERA JAYA (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this study were (1) to find out whether or not there was a significant difference in students‟ writing achievement before and after they were taught by using Draw Label Caption (DLC) strategy and (2) to find out whether or not there was a significant difference in writing achievement between the students who were taught by using Draw Label Caption (DLC) strategy and those who were not. This study was experimental research design and used quasi experimental research method that applied pre-test and post-test control group design. The population was taken from the eleventh grade students of MAN SakatigaIndralaya in academic year 2015-2016 and the number of sample was 80 students. In taking the sample, purposive sampling technique was used. The experimental group was taught by using Draw Label Caption (DLC) strategy while the control group did not receive any treatment. The data of this research were obtained by means of writing test. The writing tests in this study consisted of the pre-test and the post-test. The results of test were analyzed by using t-test: paired sample t-test and independent sample t-test. By using SPSS v.22 for Windows program, the result showed that (1) there was a significant difference in students‟ writing achievement before and after they were taught by using Draw Label Caption (DLC) strategy (mean diff=16.88, and ρ.value=.000) and (2) there was a significant difference in writing achievement between the students who were taught by using Draw Label Caption (DLC) strategy and those who were not(mean diff=8.19, and ρ .value=.000). Therefore, it can be concluded that Draw Label Caption (DLC) strategy was effective to improve students' writing achievement.